X-ray structure and EPR behavior of a new dimeric copper(II) complex with 4-amino-N-(5-methoxy-2-pyrimidinyl)benzenesulfonamide - Ellena, J. (2007)
A new complex, [Cu2(sulfameter)4]3 Æ 2.5H2O (sulfameter = 4-amino-N-(5-methoxy-2-pyrimidinyl)benzenesulfonamide), has been synthesized. Its structure has been determined by single-crystal X-ray diffraction and its spectroscopic properties (EPR, IR, Raman, UV–Vis) have been analyzed. The structure presented three different dimeric units in the unit cell and the EPR spectra, characteristic of antiferromagnetically coupled dimers, revealed two magnetically different dimeric environments.